Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.7 - Simplifying Complex Fractions - Exercise Set: 40

Answer

$\dfrac{\dfrac{4}{x}+\dfrac{x}{x+1}}{\dfrac{1}{2x}+\dfrac{1}{x+6}}=\dfrac{2(x+6)(x+2)}{3(x+1)}$

Work Step by Step

$\dfrac{\dfrac{4}{x}+\dfrac{x}{x+1}}{\dfrac{1}{2x}+\dfrac{1}{x+6}}$ Evaluate the sums indicated in the numerator and the denominator: $\dfrac{\dfrac{4}{x}+\dfrac{x}{x+1}}{\dfrac{1}{2x}+\dfrac{1}{x+6}}=\dfrac{\dfrac{4(x+1)+x^{2}}{x(x+1 )}}{\dfrac{x+6+2x}{2x(x+6)}}=\dfrac{\dfrac{x^{2}+4x+4}{x(x+1)}}{\dfrac{3x+6}{2x(x+6)}}=...$ Evaluate the division: $...=\dfrac{x^{2}+4x+4}{x(x+1)}\div\dfrac{3x+6}{2x(x+6)}=\dfrac{2x(x+6)(x^{2}+4x+4)}{x(x+1)(3x+6)}=...$ Factor the trinomial in the numerator and take out common factor $3$ from the second parentheses in the denominator. Then, simplify: $...=\dfrac{2x(x+6)(x+2)^{2}}{3x(x+1)(x+2)}=\dfrac{2(x+6)(x+2)}{3(x+1)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.